Hippocampal Synapses Depend on Hippocampal Estrogen Synthesis - Kretz, Oliver (J Neurosci, 2004)
Estrogens have been described to induce synaptogenesis in principal neurons of the hippocampus and have been shown to be synthesized and released by exactly these neurons. Here, we have focused on the significance of local estrogen synthesis on spine synapse formation and the synthesis of synaptic proteins. To this end, we reduced hippocampal estrogen synthesis in vitro with letrozole, a reversible nonsteroidal aromatase inhibitor. In hippocampal slice cultures, letrozole treatment resulted in a dose-dependent decrease of 17β-estradiol as quantified by RIA. This was accompanied by a significant decrease in the density of spine synapses and in the number of presynaptic boutons. Quantitative immunohistochemistry revealed a downregulation of spinophilin, a marker of dendritic spines, and synaptophysin, a protein of presynaptic vesicles, in response to letrozole. Surprisingly, no increase in the density of spines, boutons, and synapses and in spinophilin expression was seen after application of estradiol to the medium of cultures that had not been treated with letrozole. However, synaptophysin expression was upregulated under these conditions. Our results point to an essential role of endogenous hippocampal estrogen synthesis in the maintenance of hippocampal spine synapses.